Hacking exposed 7 network security secrets & solutions - McClure, Stuart; Scambray, Joel; Kurtz, George (McGraw-Hill, 2012)
Bolster your system's security and defeat the tools and tactics of cyber-criminals with expert advice and defense strategies from the world-renowned Hacking Exposed team. Case studies expose the hacker's latest devious methods and illustrate field-tested remedies. Find out how to block infrastructure hacks, minimize advanced persistent threats, neutralize malicious code, secure web and database applications, and fortify UNIX networks. Hacking Exposed 7: Network Security Secrets & Solutions contains all-new visual maps and a comprehensive "countermeasures cookbook."